2013
DOI: 10.1002/jcb.24497
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal protein vimentin interacts with and regulates peroxisome proliferator‐activated receptor gamma via a proteasomal degradation process

Abstract: Peroxisome proliferators-activated receptor gamma (PPARγ) receptor is a transcription factor that is located in and functions primarily in the nucleus. PPARγ is exported from the nucleus upon mitogen and ligand stimulation under certain circumstances. However, a cytoplasmic PPARγ interacting protein and its function have not been previously identified. Here, we report for the first time that cytosolic PPARγ interacts directly with cytoskeletal vimentin. We performed PPARγ immunoprecipitation followed by mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…[52][53][54] Previous studies have found that vimentin interacts with PPARγ via a proteasomal degradation process. 55 Consequently, our results showed that PPARγ could promote the mRNA expression level of vimentin, while it could be reversed by the downregulation of PPARγ. The above results suggest that a high level of FFA may promote the expression of vimentin by upregulating PPARγ, which ultimately leads to the occurrence and development of PCa.…”
Section: Discussionmentioning
confidence: 66%
“…[52][53][54] Previous studies have found that vimentin interacts with PPARγ via a proteasomal degradation process. 55 Consequently, our results showed that PPARγ could promote the mRNA expression level of vimentin, while it could be reversed by the downregulation of PPARγ. The above results suggest that a high level of FFA may promote the expression of vimentin by upregulating PPARγ, which ultimately leads to the occurrence and development of PCa.…”
Section: Discussionmentioning
confidence: 66%
“…During 3T3-L1 adipogenesis, C/EBP-α and PPAR-γ are activated by insulin with FBS in DM [ 27 , 28 ]. In addition, the experiments were conducted during adipogenesis to investigate how EF-2001 treatment regulates the expression level of transcription factors such as C/EBP-α and PPAR-γ.…”
Section: Resultsmentioning
confidence: 99%
“…We next demonstrated that STK38 could significantly slow the degradation of PPARγ, but the underlying mechanism is not known at present. Nevertheless, the level of PPARγ protein has been reported to be regulated at multiple levels by SUMOylation and ubiquitination [ 14 , 15 ], ligand-binding [ 16 ], and also protein–protein interactions [ 17 ], which directly affect its activities. In this study, we found that PPARγ was quickly degraded, whereas STK38 levels remained relatively stable after inhibition of new protein synthesis by cycloheximide [ 18 ].…”
Section: Discussionmentioning
confidence: 99%